Indicators for Homographs on the Franček Portal - Perdih, Andrej (Jezikoslovni zapiski, 2021)
This article presents the system of indicators (or signposts) designed to distinguish between homographs when searching the dictionary parts of the Franček educational language portal for Slovenian. In dictionaries, homographs (or at least homonyms) are usually assigned numbers (or indices). Because these themselves do not provide any disambiguating information, we have prepared various types of indicators, such as part-of-speech, semantic, and other types. Semantic indicators mostly include hypernyms, synonyms, and domain information, as well as other types. The key properties of semantic indicators are their disambiguating ability among homographs, comprehensibility, and brevity. The indicators are intended for the target users of the Franček portal; that is, primary- and secondary-school students.